Develop an implementation methodology of the NTP-ISO/IEC 17025: 2017 standard for the accreditation of soil, concrete and pavement test laboratories in private universities of Perú - 2018 - Duarte Lizarzaburu, María Etelvina (2019)
The purpose was to develop a methodology for the implementation of Standard NTP ISO / IEC 17025: 2017 for the accreditation of soil, concrete and pavement testing laboratories in private universities in Peru, for which the PMBOK and the requirements of Standard NTP ISO / IEC 17025: 2017. The methodology was structured into three main components: diagnosis, management, operation and maintenance, each of which contains a group of formats structured according to the regulatory requirements to be implemented. The proposed methodology is a tool to help university laboratories that aspire to be accredited, that guarantee the quality and reliability of the tests and contribute to their management as a training, research and service center. In Peru there are few accredited laboratories of universities, a problem that is reflected in the positioning of our country in terms of quality infrastructure, in this sense, the proposed methodology would be very helpful in the process of accreditation of laboratories and therefore improve the quality of the infrastructure.